Identification of Genes Associated with Familial Focal Segmental Glomerulosclerosis Through Transcriptomics and In Silico Analysis, Including RPL27, TUBB6, and PFDN5 - Mahmoud, Anfal (2024)
Focal segmental glomerulosclerosis (FSGS) is a major cause of nephrotic syndrome and often leads to progressive kidney failure. Its varying clinical presentation suggests potential genetic diversity, requiring further molecular investigation. This study aims to elucidate some of the genetic and molecular mechanisms underlying FSGS. The study focuses on the use of bioinformatic analysis of gene expression data to identify genes associated with familial FSGS. A comprehensive in silico analysis was performed using the GSE99340 data set from Gene Expression Omnibus (GEO) comparing gene expression in glomerular and tubulointerstitial tissues from FSGS patients (n = 10) and Minimal Change Disease (MCD) patients (n = 8). These findings were validated using transcriptomics data obtained using RNA sequencing from FSGS (n = 3) and control samples (n = 3) from the UAE. Further validation was conducted using qRT-PCR on an independent FFPE cohort (FSGS, n = 6; MCD, n = 7) and saliva samples (FSGS, n = 3; Control, n = 7) from the UAE. Three genes (TUBB6, RPL27, and PFDN5) showed significant differential expression (p < 0.01) when comparing FSGS and MCD with healthy controls. These genes are associated with cell junction organization and synaptic pathways of the neuron, supporting the link between FSGS and the neural system. These genes can potentially be useful as diagnostic biomarkers for FSGS and to develop new treatment options.